1984
DOI: 10.1111/j.1365-4362.1984.tb04061.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Studies of the Evolution of Physical Properties of the Human Skin with Age

Abstract: In vivo measurements taken by valid methods, help to interpret the phenomena associated with the aging process. The authors developed some routine techniques to measure physical properties of the skin both deep in the dermis-epidermis and at the surface (stratum corneum). Measurements on the forearm of 150 people yielded the following results regarding the dermis-epidermis level: (1) skin thickness begins to decrease at 45 years of age for men and women, when women's skin becomes thinner than men's skin; (2) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
98
2
3

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(112 citation statements)
references
References 14 publications
9
98
2
3
Order By: Relevance
“…Also in agreement with psychophysiological research, we observed that SC at acupoints decreases with age in both genders [19,20]. This finding generally coincides with the first clear agerelated changes in the skin of adult humans that appear between the third and fourth decades of life, changes that may be accounted for by a relatively sudden decrease in skin thickness and elasticity occurring in the fourth decade [21]. In addition, we found significantly higher afternoon SC readings in both genders, consistent with increased sympathetic autonomic nervous system activity in the afternoon [22].…”
Section: Discussionsupporting
confidence: 90%
“…Also in agreement with psychophysiological research, we observed that SC at acupoints decreases with age in both genders [19,20]. This finding generally coincides with the first clear agerelated changes in the skin of adult humans that appear between the third and fourth decades of life, changes that may be accounted for by a relatively sudden decrease in skin thickness and elasticity occurring in the fourth decade [21]. In addition, we found significantly higher afternoon SC readings in both genders, consistent with increased sympathetic autonomic nervous system activity in the afternoon [22].…”
Section: Discussionsupporting
confidence: 90%
“…C-E, osmium tetroxide; A, B, F, and G, ruthenium tetroxide. (14) alone can account for the decreased TEWL in aged epidermis. A combination of these factors could be operative.…”
Section: Discussionmentioning
confidence: 96%
“…A combination of these factors could be operative. In contrast, it has been long known that aged epidermis is abnormally permeable to a variety of drugs in in vitro systems (14)(15)(16). Thus, it seemed likely to us that the seemingly normal and even subnormal levels of TEWL displayed by intrinsically aged epidermis might mask an underlying lack of functional reserve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fitting to a line was considered appropriate because an exponential decrease in backscattered light intensity with depth occurred, yet the demodulation electronics performed a logarithmic function on the detected signal. Because previous studies have found differences in skin with age [12,13], the data were analyzed to determine whether sorting by age or sex was necessary. Images on both the forearm and upper inner arm were evaluated.…”
Section: Image Analysismentioning
confidence: 99%